Equity Capital Raising and Determinants of its Price Behaviour in Malaysia - Salamudin, Norhana (1998)
Capital investment is an important economic activity that contributes to economic growth. Aggressive capital formation leading to high economic growth can be the result of either public expenditure policies for welfare betterment or private initiatives, which enable the market mechanism to operate effectively and efficiently. In Malaysia, the private sector plays an active role in economic development, so its ability to raise external funding must not be en cumbered by restrictive policies that increases costs of financing. Thus, the first objective of this study is to search for a link between the amount of capital rises by the private sector and changes in macroeconomic factors. Time constraints limit the study to external capital funding in the form of equity only, both seasoned and unseasoned ones. Apart from relating the volume of equity raised to a certain macro economic variable,the research is extended to identifying factors in explaining the price behaviour of rights is sue announcements and listing of IPOs. This study is based on findings in the U.S. that volume and price behaviour of equity issues (particularly seasoned equity) are influenced by movement of the business cycle as measured by the National Bureau of Economic Research (NBER). Since similar index is not available in Malaysia, a proxy closely related to variations in the business cycle was used. This proxy is the term premium, which is the excess of the average 20-year Malaysian Government Securities (MGS) yield over the3-month Treasury bill (TB) yield. Evidence of a significant association between term premiums and movements of the business cycle in the U.S. is the basis, which led to the adoption of this variable in the study. The research design used in this study is the event study methodology to measure price behaviour of rights issues and IPOs, and the ordinary least square regression method to determine the variables explaining the price behaviour. The market-adjusted return was used to derive abnormal returns of rights issues.